2017
DOI: 10.3389/fcimb.2017.00077
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Staphylococcus aureus Virulence by Helcococcus kunzii in a Caenorhabditis elegans Model

Abstract: Social bacterial interactions are considered essential in numerous infectious diseases, particularly in wounds. Foot ulcers are a common complication in diabetic patients and these ulcers become frequently infected. This infection is usually polymicrobial promoting cell-to-cell communications. Staphylococcus aureus is the most prevalent pathogen isolated. Its association with Helcococcus kunzii, commensal Gram-positive cocci, is frequently described. The aim of this study was to assess the impact of co-infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…The C. elegans infection assay was performed as previously described using the Fer-15 mutant line, which has a temperature sensitive fertility defect [ 66 ]. Fer-15 was provided by the Caenorhabditis Genetics Center, which is funded by the NIH National Center for Research Resources (NCRR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C. elegans infection assay was performed as previously described using the Fer-15 mutant line, which has a temperature sensitive fertility defect [ 66 ]. Fer-15 was provided by the Caenorhabditis Genetics Center, which is funded by the NIH National Center for Research Resources (NCRR).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 30 L4 animals were placed in the center of the bacteria lawn. The number of nematodes inside or outside each lawn was counted after 16 h, as previously described [ 66 ]. The results were described in percent occupancy corresponding to the number of C. elegans in the bacterial lawn/the total number of nematodes.…”
Section: Methodsmentioning
confidence: 99%
“…Competition between commensal and pathogenic bacteria has been observed during cutaneous colonization [ 79 ]. In contrast, Helcococcus kunzii (a commensal Gram-positive coccus) and S. aureus cooperation led to a decrease of S. aureus virulence in Caenorhabditis elegans [ 80 ]. S. aureus shifts toward commensalism in response to Corynebacterium sp.…”
Section: Overview Of Biofilms In Dfumentioning
confidence: 99%
“…Due to the high homology of genes between nematodes and mammals and because nematodes have a relatively complete digestive system, C. elegans can be used as a host-pathogen interaction model in scientific research [58,59]. In this study, results demonstrated that nematodes treated with P25 had a…”
Section: Effect Of P Acidilactici P25 On the Lifespan Of C Elegansmentioning
confidence: 76%